Organizational attributes that contribute to the learning & improvement capabilities of healthcare organizations: a scoping review - Kees de Kok; Wilma van der Scheer; Corry Ketelaars; Ian Leistikow (BMC, 2023)
Abstract Background This study aims to explore and identify the organizational attributes that contribute to learning and improvement capabilities (L&IC) in healthcare organizations. The authors define learning as a structured update of system properties based on new information, and improvement as a closer correspondence between actual and desired standards. They highlight the importance of learning and improvement capabilities in maintaining high-quality care, and emphasize the need for empirical research on organizational attributes that contribute to these capabilities. The study has implications for healthcare organizations, professionals, and regulators in understanding how to assess and enhance learning and improvement capabilities. Methods A systematic search of peer-reviewed articles published between January 2010 and April 2020 was carried out in the PubMed, Embase, CINAHL, and APA PsycINFO databases. Two reviewers independently screened the titles and abstracts and conducted a full-text review of potentially relevant articles, eventually adding five more studies identified through reference scanning. Finally, a total of 32 articles were included in this review. We extracted the data about organizational attributes that contribute to learning and improvement, categorized them and grouped the findings step-by-step into higher, more general-level categories using an interpretive approach until categories emerged that were sufficiently different from each other while also being internally consistent. This synthesis has been discussed by the authors. Results We identified five attributes that contribute to the L&IC of healthcare organizations: perceived leadership commitment, open culture, room for team development, initiating and monitoring change, and strategic client focus, each consisting of multiple facilitating aspects. We also found some hindering aspects. Conclusions We have identified five attributes that contribute to L&IC, mainly related to organizational software elements. Only a few are identified as organizational hardware elements. The use of qualitative methods seems most appropriate to understand or assess these organizational attributes. We feel it is also important for healthcare organisations to look more closely at how clients can be involved in L&IC. Trial registration Not applicable.